The Results of Open-Heart Operations Performed on Children - Ferguson, Colin C. (1965)
From December 1, 1959, to January 1, 1965, a total of 166 children have undergone 168 open-heart operations at The Children's Hospital in Winnipeg, Manitoba. While this series is not a large one, the defects encountered include most of those cardiac abnormalities which are amenable to open-heart correction in children. For all operations a Kay-Cross disc oxygenator was employed. In 42 of the 168 operations, hypothermia (25-30° C.) was also used and was obtained by a Brown-Harrison heat exchanger incorporated into the arterial line. The smallest infant survivor in this series of patients weighed 8 lb. 14 oz. at the time of her operation. Of the 166 children operated upon 149 have survived, an overall survival rate of 89.8%.